Front Cover: Mirror‐Image Cofacial Coronene Dimers Characterized by CD and CPL Spectroscopy: A Twisted Bilayer Nanographene (ChemPhotoChem 11/2021). Issue 11 (28th October 2021) - Uehara, Keiji; Kano, Haruka; Matsuo, Kyohei; Hayashi, Hironobu; Fujiki, Michiya; Yamada, Hiroko; Aratani, Naoki
Abstract : The Front Cover shows Mt. Fuji, the highest mountain in Japan, reflecting off the water surface in a beautiful symmetrical form. On this image, we superimposed the mirror‐image circularly polarized luminescence (CPL) spectra of the 1, 8‐naphthylene‐linked face‐to‐face coronene dimer reported in this study. More information can be found in the Communication by Hiroko Yamada, Naoki Aratani and co‐workers .